University students complete community programme - Borneo, Post (Borneo Post, 2011)
LABUAN: The off-campus students of Universiti Utara Malaysia (UUM), Sabah Branch, completed their charity work at a disabled people centre (PDK) here last Sunday as part of their bachelor’s degree programme in Public Administration.